Clinical outcomes and resource utilisation in Medicare patients with chronic liver disease: a historical cohort study. Issue 5 (16th May 2014) - Younossi, Zobair M; Zheng, Li; Stepanova, Maria; Venkatesan, Chapy; Mishra, Alita
Abstract : Objective: The aim of this study is to assess recent trends in health resource utilisation and patient outcomes of Medicare beneficiaries with chronic liver disease (CLD). Setting: Liver-related mortality is the 10th leading cause of death in the USA, and hepatitis C virus (HCV) and obesity-related non-alcoholic fatty liver disease are the major causes of CLD. As the US population ages and becomes more obese, the impact of CLD is expected to become more prominent for the Medicare population. Participants: This is a retrospective cohort study of Medicare beneficiaries with a diagnosis of CLD based on inpatient (N=21 576; 14 977 unique patients) and outpatient (N=515 990; 244 196 patients) claims from 2005 to 2010. Primary and secondary outcome measures: The study outcomes included hospital length of stay (LOS) and inpatient mortality as well as inpatient and outpatient inflation-adjusted payments. Results: Between 2005 and 2010, there was an annual decrease in LOS of 3.17% for CLD-related hospitalisations. Risk-adjusted in-hospital mortality decreased (OR 0.90, 95% CI 0.87 to 0.94), while short-term postdischarge mortality remained stable (1.00, 0.98 to 1.03). Inpatient per-claim payment increased from 11 769 in 2005 to 12 347 in 2010 (p=0.0006). Similarly, the average yearly payments for outpatient care increased from 366 to 404 (p<0.0001). This change in payment was observed together with a consistent decrease in the proportion of beneficiary-paid amount (25.4–20%, p<0.0001) as opposed to Medicare-paid amount (73.1–80%, p<0.0001). The major predictors of higher outpatient payments were younger age, Asian race or Hispanic ethnicity, living in California, and having more diagnoses and outpatient procedures per claim. The predictors of inpatient spending also included younger age, location and the number of inpatient procedures. Conclusions: Length of inpatient stay and inpatient mortality among Medicare beneficiaries with CLD decreased, while inpatient and outpatient spending increased.